Ecological niche modelling as a tool to identify candidate indigenous chicken ecotypes of Tigray (Ethiopia) - Gebru, Gebreslassie; Belay, Gurja; Vallejo-Trujillo, Adriana; Dessie, Tadelle; Gheyas, Almas; Hanotte, Olivier (Frontiers in Genetics, 2022)
The Tigray region is an ancient route of entry for domestic chicken into Africa. The oldest African chicken bones found in this region at Mezber, a pre-Aksumite rural farming settlement, dated around 800-400 BCE. Since then, the farming communities of the region have been integrated chicken into their livelihoods and recognised for its higher chicken-to-human population ratio. The region is also recognised by its diverse and complex geography, which varies from 500 to 4000 meters above sea level (m.a.s.l.) with more than 15 agro-ecological zones. Following these introductions, it has been estimated that the genetic integrity of these local Tigrayan chicken populations has been diluted by 17% compared to the 15% and 9% for the Amhara and Oromia regions, respectively. This calls for the rapid characterisation of indigenous Tigrayan chicken and their habitats to provide relevant baseline information, guiding conservation and breeding improvement initiatives. Hence, studying the habitats and defining the potential chicken ecotypes in the Tigray region will provide insight into where and what to conserve. This study employed Ecological Niche Modelling (ENM) using MaxEnt to characterise the habitats of 16 indigenous village chicken populations of Tigray. A total of 34 ecological and landscape variables: climatic (22), soil (eight), vegetation, and land cover (four) were included. To select the most contributing and uncorrelated variables, we applied Principal Component Analysis (PCA), correlation, and MaxentVariableSelection (MVS) procedures. The selected variables were three climatic (bio5 = maximum temperature of the warmest month, bio8 = mean temperature of the wettest quarter, bio13 = precipitation of the wettest month), three vegetation and land cover (grassland, forest land, and cultivated land proportional areas), and one soil (clay content) ones. Following our analysis, we identified four chicken agro-ecologies defining four indigenous Tigrayan chicken ecotypes. The proportion of cultivated land and bio5 were the most frequent describing the ecotypes, whereas bio13, bio8, soil clay content, forest and grass/shrub cover were variables that created heterogeneity across ecotypes. This study will guide the conservation of the endangered indigenous Tigray chicken ecotypes while providing a standardised framework for new studies on the environmental characterisation of livestock populations.